Challenge and Opportunity of Marketing Digital-Based for Business Owners During Pandemic in Indonesia - Endrawati, Titin; Bangkara, B.M.A.S. Anaconda; Irdiana, Sukma; Antoni, Antoni; Siregar, Ade Perdana (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
Challenges and opportunities in marketing businesses relying on digital applications during the pandemic have been felt to be very diverse and complex. The study aimed to obtain scientific evidence of the challenges and opportunities of digital application-based business marketing. We discussed them under a phenomenological approach where we sought answers to gain a new understanding of a phenomenal event, namely marketing during a pandemic. To get the information, we needed to visit various sources of information, and we studied with a literature review system that involved data coding, evaluation, and interpretation of data. We did a virtual search of the data on several publications related to economic-based digital marketing issues during the pandemic. Finally, we concluded intending to get valid answers. Our data search was carried out electronically on several sources with a publishing period between 2010 and 2022 based on the results. After reviewing various sources and discussing them, we can conclude that digital-based marketing for a profitable and sustainable business has undoubtedly been proven to face many challenges and opportunities. The question mark is that not all business people and customers understand and can apply point technology, while the opportunity is that digital technology applications can innovate business marketing efforts efficiently, effectively, and productively.